#TITLE_ALTERNATIVE# - NUGRAHA (NIM 10205031), NURDIN
Indications showed that the geothermal manifestations in the form of surface eruption of hot water, fumaroles, solfatar, mofet and the presence of rock hydrothermal change in the surface. Manifestation of this can be used to determine the potential or the characteristics of geothermal, which is involved with fluid, gas and isotope to be learned by using the geo chemical engineering. Geochemistry techniques can be used to determine the temperature of water in the geothermal reservoir, geothermal fluid type, and origin of geothermal water reservoir. In determining the temperature geothermal can be used fluid and gas samples taken from the manifestation, to determine the type of geothermal fluid can use fluid womb or composition of the geothermal manifestations, while to determine the origin of geothermal water reservoir can be determined using the actual gas and isotope. In this final task, the application of geo chemical technique is done to know the origin of geothermal water reservoir by using the isotope O-18 and H-2.